PERANCANGAN ARSITEKTUR ENTERPRISE PERGURUAN TINGGI MENGGUNAKAN TOGAF ADM (STUDI KASUS STP SAHID JAKARTA) - Sefrika Entas (Paradigma, 2016)
The business processes in the world of education requires the universities to be able to manage the information properly and will need the respective information interested parties can be met quickly and precisely. Development of EA (Enterprise Architecture) in college is a big job and full of challenges. STP Sahid Jakarta have problems in the exchange of information between the units that make external reporting a particular unit is difficult to do so spend a long enough time. Reporting is done by sorting through incoming files based on the unit and then in the process of making the information required by stakeholders (stakeholders) are not easy to come by and the old academic services as well as the lack of ICT use. Existing technology platform currently supports future applications but need additional and improved technology by optimizing the existing technology.Completion of the authors propose analyzed using TOGAF (The Open Group Architecture Framework) to create a strategic plan proposal information systems in order to align the vision and mission to improve the efficiency of services and supports the organization's strategic plan. TOGAF is a complex framework that is able to meet all the needs in the development of EA. process steps in the development of enterprise architecture based on the IT infrastructure. The results of this study will produce an EA blueprint that can be used by STP Sahid Jakarta in constructing an architecture of Information System / Information Technology